Fostering EFL Students' Pragmatic Competence Through Flipped-STAD Learning: A Study of ELT in an Islamic Higher Education Context - Muliyah, Pipit; Margana, Margana; Ciptaningrum, Dyah Setyowati; Hawanti, Santhy; Hakim, Lystiana Nurhayat; Danial, Muhammad (UIN Salatiga, 2025)
This study investigated the impact of integrating Flipped Learning (FL) and Student Team Achievement Division (STAD) on the pragmatic competence of English as Foreign Language (EFL) students, with a particular focus on their pragmalinguistic competence related to making requests and refusals. Conducted in an Islamic higher education setting, this research addresses a gap in the existing literature, as the combined effect of FL and STAD on pragmatic competence remains underexplored. The study aimed to empirically assess the influence of this integrated pedagogical approach and examining students' perceptions of its effectiveness. The research gathered quantitative and qualitative data using a sequential explanatory mixed-methods design. Initially, quantitative data were collected from pre- and post-test scores using a two-group experimental design (experimental group N=28, control group N=28). Discourse Completion Tests (DCTs), focusing on requests and refusals, were employed to evaluate pragmatic competence. Subsequently, semi-structured interviews with eight students from experimental group were conducted to delve into their perceptions. ANCOVA statistical analysis revealed that the flipped-STAD group significantly outperformed the control group on post-test scores, demonstrating its effectiveness for enhancing pragmatic competence in requests and refusals. In contrast, the control group received traditional teacher-centred instruction, which limited opportunities for interactive pragmatic practice. This comparison between student-centred and teacher-centred methods might inherently favour the interactive approach. The findings from the Interviews indicated that students had positive perceptions of flipped-STAD for developing pragmalinguistic competence. Thus, flipped-STAD seems a promising strategy for enhancing pragmatic competence in EFL, offering educators with an effective method. However, further research is needed to compare it with other student-centred approaches.